Narrative Writing Game A Reading Of The Novel A Woman's Hymn...Twilight of The Sea By The Novelist Saad Muhammad Rahim (Journal of the College of Basic Education, 2024)
This study, titled (The Narrative Writing Game), is a reading of the novel Hymn to a Woman... Twilight of the Sea by the writer Saad Muhammad Rahim. It seeks to explain the concept of the process of artistic creativity in general, and novelistic creativity in particular, as it is one of the mental processes through which the creator is able to create new and unique models of writing. Its type, and this is what we found in this novel, through which the writer played his novelistic or narrative game with the reader through the use of different writing techniques in the course of events and the transformation of times, places, style of dialogue, etc., in addition to the writer including his original novel with a new novel and the events and characters in it. New, so this research came to talk about the writer’s game in employing characters, places, and events to be intertwined between the two novels.